Makna Motivasi Berprestasi bagi Penyandang Difabel dalam Buku Inilah Jihadku - Yusril Yasin; Saifullah (Fakultas Dakwah Universitas Ibrahimy, 2023)
The book This Is My Jihad is a book of life stories by the author Muhammad Zulfikar Rahmat, who tells his life story, the story of a person who was born with disabilities or disabilities. He tells the story of a dream fighter, a person with disabilities who tries to fight against obstacles and tests in order to realize his goals and dreams. The phenomenon of disabilities in general has many obstacles both individually and in groups, such as barriers to mobility, mentality, feeling inferior, lacking self-confidence, being isolated, experiencing awkwardness in carrying out social functions, not being able to get along normally, not being able to communicate well, not being able to participate in development activities. The purpose of this research is to describe the meaning of achievement motivation for people with disabilities in the book This Is My Jihad. The method used is a qualitative method with a hermeneutic type of research, and the data analysis uses the objectivist hermeneutics cycle of the partwhole line from Gadamer. The results of research on the meaning of motivation for people with disabilities in the book This Is My Jihad found three meanings of motivation: perseverance, positive thinking and patience.